Effects of school-based mindfulness intervention on health-related quality of life: moderating effect of gender, grade, and independent practice in cluster randomized controlled trial - Lassander Maarit; Hintsanen Mirka; Suominen Sakari; Mullola Sari; Vahlberg Tero; Volanen Salla-Maarit (SPRINGER, 2022)
Object
We investigated the impact of a school-based 9-week mindfulness program vs. active control program (relaxation) and inactive control group on children's self-reported Health-Related Quality of Life (HRQoL) moderated by gender, grade, and independent practice.
Method
In total 3519 (50/50% boys/girls) Finnish students aged 12-15 years from 56 schools were randomized into mindfulness intervention, active, and inactive control groups. HRQoL was measured at baseline, at 9 weeks, and at 26 weeks and analyzed with multilevel linear modeling.
Results
Significant improvement on HRQoL was found (β = mean difference) (β = 1.587, 95% CI 0.672-2.502, p < 0.001) after 9 weeks and at 26 weeks of follow-up among students in the mindfulness group as compared to the active control group. Moderating effects on HRQoL were found for gender, grade, and independent practice: girls, 7th and 8th grade students, and students with regular independent mindfulness practice benefited most.
Conclusions
Gender and developmental stage may moderate the effects of mindfulness interventions on HRQoL and offer guidance in designing effective promotive interventions for children and adolescents.